The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2466/02.07.17.pr0.110.2.639-644
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Self-Assessment Bias in Mental Health Providers

Abstract: Previous research has consistently found self-assessment bias (an overly positive assessment of personal performance) to be present in a wide variety of work situations. The present investigation extended this area of research with a multi-disciplinary sample of mental health professionals. Respondents were asked to: (a) compare their own overall clinical skills and performance to others in their profession, and (b) indicate the percentage of their clients who improved, remained the same, or deteriorated as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
278
1
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 383 publications
(310 citation statements)
references
References 18 publications
18
278
1
13
Order By: Relevance
“…Such an assumption would mean that clinicians would perceive little reason to focus on monitoring, maintaining, and improving their skills and outcomes. Walfish, McAlister, O'Donnel, and Lambert (2012) found evidence to support this hypothesis. In a cohort of psychological therapists, the mean self-rated skill level relative to colleagues was high, with the mean rating being at the 80 th centile (rather than the 50 th , as should be the case).…”
Section: Disordersmentioning
confidence: 93%
See 3 more Smart Citations
“…Such an assumption would mean that clinicians would perceive little reason to focus on monitoring, maintaining, and improving their skills and outcomes. Walfish, McAlister, O'Donnel, and Lambert (2012) found evidence to support this hypothesis. In a cohort of psychological therapists, the mean self-rated skill level relative to colleagues was high, with the mean rating being at the 80 th centile (rather than the 50 th , as should be the case).…”
Section: Disordersmentioning
confidence: 93%
“…This overestimation of ability is found in a range of skills, such as driving and job performance (e.g., Anderson, Warner, & Spencer, 1984;Meyer, 1990), and is known as 'self-assessment bias'. Furthermore, when asking these clinicians about how many of their patients recovered or improved, Walfish et al (2012) found that clinicians believe that most of their clients recover after therapy. In a similar vein, Brosan, Reynolds, and Moore (2008) found that, overall, therapists' self-ratings have no more than moderate agreement with independent ratings of their competence.…”
Section: Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, we focused not only on depression (Barnes et al, 2013; French et al, 2017; Hundt et al, 2013) but included different diagnoses, which also implied heterogeneity. Study limitations refer to the small accidental sample size, reactivity due to an awareness of being interviewed, self-assessment bias (Walfish, McAlister, O’Donnell, & Lambert, 2012), patient selection by therapists (which is why it remains unclear whether prototypical or especially cooperative patients were included), of therapies mainly in the early stages, and the restriction to a university treatment setting. In future studies, learning and skills use could be addressed routinely and repeatedly as a complete survey within a certain time period, both to reduce bias, and to underscore the importance of skills use.…”
Section: Discussionmentioning
confidence: 99%